Technetium-99m-labeled stealth pH-sensitive liposomes: a new strategy to identify infection in experimental model - Carmo,Vildete Aparecida Sousa (2007)
The diagnosis of inflammatory and infectious processes is an important goal in medicine. The use of radiopharmaceuticals for identification of inflammation and infection foci has received considerable attention. The aim of this work was to evaluate the uptake and the imaging potential of stealth pH-sensitive liposomes radiolabelled with 99mTechnetium (99mTc) to identify infection sites in mice. The liposomes containing glutathione were labeled with 99mTc-Hexamethylpropyleneamine oxime (HMPAO) complex. The 99mTc-labeled stealth pH-sensitive liposomes (99mTc-SpHL) were injected in mice bearing infection in the right thigh muscle induced by Staphylococcus aureus. Biodistribution studies and scintigraphic imaging were performed at different times after injection of radiopharmaceutical. The 99mTc-SpHL was significantly uptaken by abscess when compared to the respective control. The abscess was visualized as early as 0.5 hours after injection of 99mTc-SpHL becoming more prominent with the time. These results indicate that 99mTc-SpHL is a promising radiopharmaceutical for visualizing infection foci in patients.